Design and manufacture of an automatic sequential rain sampler: Testing with sub-events - (:unkn) unknown (My University, 2008)
The preliminary goal of this study is to design, construct and test an automatic sequential precipitation sampling instrument. Testing includes collection of sequential precipitation samples, analyzing them and trying to find the sources of environmental pollution. Proposed sequential sub-event sampler is composed of two parts; mechanic and electronic hardware. Mechanical part includes a stepped 100 ml sampler cups on it, and a metallic body. Electronic part is composed of digital and analog sensors, various electronic materials and a computer as the main controller of the system. Commands generated by the computer or received from the internet, control the system, and sub-event sampling period and volume can be modified. Besides the volume and time controlled sampling, intelligent control and sampling is possible by developing adequate algorithms. Since the system consists of automatic sensors that can be controlled by the computer, anthropogenic errors in sampling are expected to be kept at minimum. The proposed instrument is open to development and additions can easily be made. The developed equipment was used to collect samples for one sub-event took place on 8th of September 2007 and the samples were analyzed for pH, Ca2+, Mg2+, K+, Na+, to obtain the temporal variation of the chemical composition during the precipitation event.
Keywords: Acid precipitation; Sequential sub-event sampler